2020
DOI: 10.1192/bjo.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of the expansion of a hospital liaison psychiatry service on patient care and costs following emergency department attendances for self-harm

Abstract: Background In September 2014, as part of a national initiative to increase access to liaison psychiatry services, the liaison psychiatry services at Bristol Royal Infirmary received new investment of £250 000 per annum, expanding its availability from 40 to 98 h per week. The long-term impact on patient outcomes and costs, of patients presenting to the emergency department with self-harm, is unknown. Aims To assess the long-term impact of the investment on patient care outcomes and costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Indeed, a recent evaluation found that the introduction of the clinical programme was associated with a significant increase in referral, particularly in hospitals that had limited pre-existing resources for caring for those presenting with self-harm. Consistent with this, the availability of dedicated staff has been shown to be associated with improved care for self-harm in an ED in the UK [27]. Central components of the clinical programme include the provision of a biopsychosocial assessment and appropriate follow-up and referral to secondary mental healthcare, as well aspects it was not possible to capture in this study including the provision of an emergency care plan, collaboration with next of kin, and the provision of a 24hr phone call.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, a recent evaluation found that the introduction of the clinical programme was associated with a significant increase in referral, particularly in hospitals that had limited pre-existing resources for caring for those presenting with self-harm. Consistent with this, the availability of dedicated staff has been shown to be associated with improved care for self-harm in an ED in the UK [27]. Central components of the clinical programme include the provision of a biopsychosocial assessment and appropriate follow-up and referral to secondary mental healthcare, as well aspects it was not possible to capture in this study including the provision of an emergency care plan, collaboration with next of kin, and the provision of a 24hr phone call.…”
Section: Discussionmentioning
confidence: 66%
“…The difference between the observed and counterfactually expected trends in the post-NPP period can be interpreted as the causal impact of the intervention. This method can reduce bias in natural experiment studies where there is no randomization of exposure [11][12][13] Data and assumptions used for the economic evaluation of the NPP are described in the following sections.…”
Section: Discussionmentioning
confidence: 99%

PReCePT Devolved Nations Evaluation Report

Edwards,
Sillero Rejon,
Pithara-McKeown
et al. 2024
Preprint
“…Studies employing these designs have primarily utilised hospital records and data recorded via self-harm registries. [13][14][15][16][17][18][19] However, a systematic review that examined aspects of routine clinical care following self-harm (eg, hospital admission or specialist follow-up) found little evidence for their role in reducing repeat self-harm and suicide, 20 despite evidence from individual studies being used to inform several guidance. 21 22 The reasons for a lack of evidence from observational studies may reflect the size and representativeness of the samples used, the quality of study design, as well as the consistency, quality and range of outcomes used.…”
Section: Open Accessmentioning
confidence: 99%